A Simple and Cost‐Effective Method for the Regioselective Deuteration of Phenols. Issue 15 (17th April 2015) - Zhan, Miao; Xu, Ruixue; Tian, Ye; Jiang, Hongxia; Zhao, Lifeng; Xie, Yongmei; Chen, Yuanwei
Abstract: A highly effective and operationally simple method for the deuteration of phenols using NaOH as a catalyst and D2 O as the deuterium source is presented. A high regioselectivity for the ortho and/or para hydrogens relative to the oxygen atom was achieved, as well as a high degree of deuterium incorporation. The method also has a high functional‐group tolerance, and allowed the deuteration of complex pharmaceutically interesting substrates. Abstract : An efficient method for the synthesis of regioselectively deuterated phenols under microwave irradiation was developed. The method also allowed the deuteration of complex pharmaceutically interesting substrates.